The Evolution of Antarctic Tourism and its Relation with National and Provincial Public Policies - Vereda, Marisol; Jensen, Marie; Fontana, Pablo G. (Mar del Plata: Facultad de Arquitectura Urbanismo y Diseño Universidad Nacional de Mar del Plata, 2019)
This contribution aims to analyse the behaviour of Antarctic tourism through Ushuaia, province of Tierra del Fuego, Antártida e Islas del Atlántico Sur, as the main gateway city for Antarctic seaborne tourism, considering public policies from both the National and Provincial governments in different periods. In this regard, a periodization is presented from 1958 to 2018, identifying different phases according to the tourism area life cycle model (Butler, 1980). Methodology comprises a qualitative approach through documental analysis and in-depth interviews to key actors related to the organization of voyages and also public administration. Among results, different moments can be seen, the role played by the National State in the promotion of voyages, the gradual incorporation of the private national sector, the consolidation of Antarctic tourism by foreign private companies and the positioning of Ushuaia as a gateway due to the implementation of public policies together with the actions of private local agents. ark:/s22508112/dhrpz/a:k El propósito de esta contribución es analizar el comportamiento del turismo antártico a través de Ushuaia, provincia de Tierra del Fuego, Antártida e Islas del Atlántico Sur, como principal puerta de entrada de los flujos marítimos, en su relación con las políticas del Estado Nacional y Provincial en diferentes periodos. En este sentido, se presenta una periodización que abarca desde 1958 hasta 2018, identificando distintas etapas de acuerdo al modelo de ciclo de vida del producto turístico de Butler (1980). La metodología utilizada comprende un enfoque cualitativo a partir del análisis de documentos y entrevistas en profundidad a actores relevantes relacionados con la organización de viajes y gestión pública. Entre los resultados obtenidos se destaca el reconocimiento del rol del Estado Nacional en la promoción de los viajes, la paulatina incorporación del sector privado de origen nacional, la consolidación del turismo antártico por parte del sector privado extranjero y el ...